Acquirer Driven Digital Engineering Transformation. Issue 1 (12th April 2022) - Robinson, Kevin; Liddy, Tommie
ABSTRACT: Digital Engineering, like any initiative, should have a clear purpose and direction. For organisations that sit as Acquirers/Clients the Digital Transformation may not seem immediately valuable. However, for this group Digital Engineering can provide opportunities to tightly engage with their supplier network, understand trade‐offs through design and upgraded lifecycles and enhanced supplier outcomes. This paper discusses the benefits and challenges of adopting Digital Engineering in the Concept Phase, where most of the project costs are committed. It highlights that the greatest return on investment for Digital Engineering is during Concept Phase as the flow of authoritative information permeates the remainder of the lifecycle. This presents the case for acquisition agencies to both drive the application of Digital Engineering within their industry and lead by example, through Digital Engineering adoption.